DAGUSIBU and TOGA socialization: Improving the success of self-medication - Putu Gita Maya Widyaswari Mahayasih; Wilson Gunawan; Putri Nuraini Sutomo; Vallenchesa Susanto Theo; Devin Winata; Ade Novitasari; Yulia Katuuk; Listi Maslia Putri; Nur Lisa Anggraini (Universitas Muhammadiyah Magelang, 2024)
This community service program was conducted in the RT02/RW01 area, Palmerah Sub-district, West Jakarta. It involved providing socialization to the community regarding TOGA (family medicinal plants) and DAGUSIBU (obtain, use, store, dispose of medicine properly) with the aim of increasing public knowledge about TOGA and the proper use of medicines. The method used was direct socialization to partners and indirect education through the delivery of information via print media such as posters on village bulletin boards. The result of this community service activity was an increase in residents' knowledge about how to obtain, use, store, and dispose of medicines properly. Community knowledge regarding TOGA that can be used for treatment also increased.